The phosphoproteome of choroid plexus epithelial cells following infection with Neisseria meningitidis - Herold, Rosanna; Denzer, Lea; Muranyi, Walter; Stump-Guthier, Carolin; Ishikawa, Hiroshi; Schroten, Horst; Schwerk, Christian (Frontiers in Cellular and Infection Microbiology, 2023)
The Gram-negative bacterium Neisseria meningitidis, which causes meningitis in humans, has been demonstrated to manipulate or alter host signalling pathways during infection of the central nervous system (CNS). However, these complex signalling networks are not completely understood. We investigate the phosphoproteome of an in vitro model of the blood-cerebrospinal fluid barrier (BCSFB) based on human epithelial choroid plexus (CP) papilloma (HIBCPP) cells during infection with the N. meningitidis serogroup B strain MC58 in presence and absence of the bacterial capsule. Interestingly, our data demonstrates a stronger impact on the phosphoproteome of the cells by the capsule-deficient mutant of MC58. Using enrichment analyses, potential pathways, molecular processes, biological processes, cellular components and kinases were determined to be regulated as a consequence of N. meningitidis infection of the BCSFB. Our data highlight a variety of protein regulations that are altered during infection of CP epithelial cells with N. meningitidis, with the regulation of several pathways and molecular events only being detected after infection with the capsule-deficient mutant. Mass spectrometry proteomics data are available via ProteomeXchange with identifier PXD038560.